Oscillation criteria for nonlinear second-order differential equations with damping - Çakmak, D. (Український математичний журнал, 2008)
Some new oscillation criteria are given for general nonlinear second order ordinary differential equations with damping of the form x′′ + p(t)x′ + q(t) f (x) = 0, where f is with or without monotonicity. Our results generalize and extend some earlier results of Deng.